Physicochemical Properties of Handere Clays and Their Use as a Building Material - Yasin Erdoğan (Journal of Chemistry)
Handere clay deposits were discovered at Adana in Turkey. These clay units primarily consist of uncoloured claystone, pebbly sandstone, sandstone, siltstone, and mudstone marl and include gypsum lenses and clay levels of various thicknesses in places. The physicochemical properties of these clays have been investigated by different techniques including Scanning Electron and Elemental Analysis (SEM and EDS), mineralogical analyses, chemical and physical analyses, X-ray diffraction (XRD), thermogravimetric differential thermal analysis (TG-DTA), and Atterberg (Consistency) Limits Test. The mineralogical composition deduced from XRD is wide (smectite + palygorskite + illite ± feldspar ± chlorite ± quartz ± calcite ± serpentine) due to the high smectite contents (≈85%). SEM studies reveal that smectite minerals are composed of irregular platy leaves and show honeycomb pattern in the form of wavy leaves in places. The leaves presenting an array with surface edge contact are usually concentrated in the dissolution voids and fractures of volcanic glass. Organic matter content and loss on ignition analysis of raw materials are good for all the studied samples. In summary, Handere clays can be used as building materials in bricks, roof tiles, and cement and as a binder.